The role of the university in a regional innovation system (Journal of Economic Research & Business Administration, 2018)
The article discusses the changing role of the modern university in connection with the development of an innovative economy and the transfer of knowledge on an international scale. The transition to modern production, based on advanced technologies and characterized by high technology-intensiveness, makes new demands on the field of higher education. The role of higher education institutions as a source of innovative developments in the country, as well as training centers for the innovation economy, is growing. The University acts as one of the main elements of the innovation system of the region, participating in the generation, accumulation and dissemination of knowledge. Along with business and government, the university determines the structure of the regional innovation system, influencing thesocio-economic development of the region.The authors considered the main participants of the regional innovation system, their role in the formationof the regional ecosystem. The article shows that the interaction of the university and the regionalinnovation system can lead to the emergence of positive effects for all participants of RIS, which arise asa result of the formation of a single industrial ecosystem. The main positive effects from the ecosystemdevelopment for the economy of the region, higher educational institutions, as well as graduates arehighlighted. The authors have revealed the formation of the innovation infrastructure in the universitiesof the Republic of Kazakhstan, which is the foundation for the inclusion of the university in the innovationprocesses of the region. The features of various elements of the innovation infrastructure, whichallow the university to integrate into regional innovation processes, are revealed. The composition ofthe innovation infrastructure of leading universities, which occupy the first four places in the ranking ofuniversities QS-2019 in the Republic of Kazakhstan, is considered. The main tasks of the functioning ofcommercialization offices in universities of the republic are determined.